A graphene wrapped hair-derived carbon/sulfur composite for lithium–sulfur batteries1. Issue 18 (14th May 2015) - Yu, Mingpeng; Li, Rui; Tong, Yue; Li, Yingru; Li, Chun; Hong, Jong-Dal; Shi, Gaoquan
<x xml:space="preserve">Abstract</x> A hair-derived carbon/sulfur composite was wrapped with reduced graphene oxide sheets and used as the cathode for lithium–sulfur batteries, exhibiting superior cycling stability, good rate capability and high coulombic efficiency.